THE FISHERY OF NAGARJUNASAGAR, ON THE RIVER KRISHNA, DURING 1976-80. - Ramakrishnaiah, M (Indian Journal of Fisheries, 2011)
The fishery of Nagarjunasagar reservoir during 1976-80 is presented. P.pangasius, M. aor, S. childreni and L. fimbriatus, species native to the riverKrishna, formed the mainstay of the fishery. There has been a shift in the relativeabundance between carps and catfishes, the former dominating during the earlierperiod and the latter during the later period. The probable reasons for the lowfish productivity have been indicated.